The Determinants of Bank Profitability: How Malaysian Islamic Banks Response to the Financing Risk - Mohamad, Mohammad Taqiuddin; Sulaiman@Mohamad, Ahmad Azam; Khairul Hamimah; Muslim, Nazri (Advances in Social Sciences Research Journal, 2019)
The purpose of this article is to investigate the relationship between financing risk and profitability of Malaysian Islamic banks to find the impact of financing risk on bank profitably in achieving high level of stability. A regression analysis is built on an unbalanced panel data set comprising 175 observations of 17 top Malaysian Islamic banks over the period 1994-2015. To this end, the empirical data are collected from individual Islamic banks’ financial statements as submitted to the Central Bank of Malaysia for supervisory purposes. Complementary sources include the Global Market Information Database, the World Bank’s Annual Report through the International Monetary Fund (IMF), Statistical, Economic and Social Research and Training Center for Islamic Countries (SESRTCIC) and Asian Development Bank (ADB). All the determinant variables included in the model have statistically significant impacts on Malaysian Islamic banks’ profitability. However, the effects are not uniform across profitability measures. Regression findings reveal that capital ratio, financing loss provision and liquidity ratio significantly affect the profitability of Islamic banks. Some variables of monetary policy variables such as interest rate and interbank rate have a significant role on the Islamic banks’ profitability. Interestingly, there is a difference of the two variables where interest rate shown negative sign while positive sign from interbank rate. Findings also suggest the economic conditions factors such as GDP growth and unemployment also affects the profitability of Islamic banks despite the sign is different.